PENGEMBANGAN MEDIA VIDEO IKLAN LAYANAN MASYARAKAT DENGAN CERDIK SEBAGAI PENCEGAHAN DIABETES MELITUS PADA REMAJA KELAS XI - Shalihin, Nabila Idznia; Lestari, Febri Sri (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Diabetes is not only a risk for adults, but is also a risk for teenagers. The prevalence of Diabetes Mellitus based on doctor's diagnosis in West Java Province in the 15-24 year age group is 12,094 people. This is because they carry out unhealthy lifestyle behaviors. Therefore, overcoming the problem of Diabetes Mellitus can be done through health promotion regarding the prevention of Diabetes Mellitus through CERDIK behavior in the form of public service advertising videos with novelty in terms of visuals, development methods, material content, storyline, targets, and duration. Objective: Develop CERDIK Community Service Advertisement Video Media to prevent Diabetes Mellitus in class XI teenagers. Methodology: This research is an R&D (Research and Development) development research with a 4D model (Define, Design, Development, Disseminate). The total sampling number was 59 teenagers XI grades from Bandung City High School. Data analysis was carried out using interview and questionnaire techniques. Results: The media feasibility test by media experts showed a result of 82%, including in the very feasible category, the material feasibility test by material experts showed a result of 92%, including the very feasible category, and the results of the material and media feasibility test showed that 87% of users rated it as very feasible and 13% rated worthy. Conclusion: The video media for public service advertisements with CERDIK is very suitable to be used as an educational medium for preventing Diabetes Mellitus in XI grade high school teenagers.